Einfluss des Images von Bio-Produkten auf den Absatz der Erzeugnisse; The influence of the image of organic products on market development - Johannes Simons; Carl Vierboom; Ingo Har̈len (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– According to several surveys organic products widely meet consumers demand, but the corresponding market share in Germany is less than 2,5 %. Missing confidence in the authenticity of organic products, high prices compared to other foods, a low density of distribution, and a lack of a uniform label are regarded as hampering factors for market growth. The influence of the image of organic products on market development, however, is analyzed insufficiently by now. This paper therefore aims at investigating the implications of the image of organic foods on its acceptance by consumers and deriving hints for the development of the market. The actual study is based on a concept of morphological market research, the results refer to Germany and can be summarized as follows. 1. The tradition of the image of organic products is closely associated with the production methods and some kind of ascetic lifestyle. Using those products is classified as part of this lifestyle. Consumers are impressed by a concept of living that is regarded as fundamental. On the other hand perceived changes of the products and prospects for future developments are of less relevance for the image. 2. Consumers' blending of organic products and the ascetic lifestyle might be an important explanation for the low market share of organic products. 3. Positioning organic products within a market segment of tasteful foods necessarily needs to detach the connection between organic products and the "organic lifestyle". This is possible by co-operating with strong brands for example on the market of frozen food or baby food. 4. Moreover, sales opportunities could arise in the segment for wellness-products because organic products are regarded as healthy and thus meet the demands for products in this segment. In any case, one might take into account the competition with other constitutional foods that are produced in a substantially different way, as e.g. dietary supplement or functional-food. Thus a strategy to benefit from these market opportunities could result in severe problems with the supplying farmers.
Keywords: 330; Bio-Lebensmittel; Markenimage; Marktforschung; Deutschland